Evidence‐Based Practice Culture and Mentorship Predict EBP Implementation, Nurse Job Satisfaction, and Intent to Stay: Support for the ARCC© Model. Issue 4 (26th July 2021) - Melnyk, Bernadette Mazurek; Tan, Alai; Hsieh, Andreanna Pavan; Gallagher‐Ford, Lynn
Abstract: Background: The Advancing Research and Clinical practice through close Collaboration (ARCC © ) Model is a system‐wide framework for implementing and sustaining evidence‐based practice (EBP) in hospitals and healthcare systems. The model involves assessing organizational culture and readiness for EBP in addition to the development of a critical mass of EBP mentors who work with point‐of‐care clinicians to facilitate the implementation of evidence‐based care. Determining how the various components of the ARCC © Model relate to one another is important for understanding how EBP culture and mentorship impact EBP implementation, nurses' job satisfaction, and intent to stay. Aims: The current study aimed to test a model that could explain the relationships and direct pathways among eight key variables in the ARCC © Model: (1) EBP culture, (2) mentorship, (3) knowledge, (4) beliefs, (5) competency, (6) implementation, (7) nurses' job satisfaction, and (8) intent to stay. Methods: Structural equation modeling was used to test relationships among the variables in the ARCC © Model with data obtained from an earlier cross‐sectional descriptive study with 2, 344 nurses from 19 hospitals and healthcare systems across the United States. Results: The final structural equation model found that EBP culture and mentorship were key variables that positively impacted EBP knowledge, beliefs, competency, implementation, job satisfaction, and intent to stay among nurses. Linking Evidence to Action: As described in the ARCC © Model, establishing a strong sustainable EBP culture along with a critical mass of EBP mentors is crucial for the development of EBP competency and consistent implementation of evidence‐based care by nurses. A strong EBP culture along with EBP mentorship also can result in higher job satisfaction and intent to stay. Implementation of the ARCC © Model is a key strategy in assisting systems to reach health care's Quadruple Aim.